'Pilsnerisch' reden Dokumentation, Popularisierung und Inszenierung einer städtischen Umgangssprache als 'lieu de mémoire' - Boris Blahak (Brünner Beiträge zur Germanistik und Nordistik, 2019)
The article presents an investigation of the special vocabulary of German origin in Jan Hajšman's "Plzeňsko-český slovník" (2017) for lexical, phonetic and morphological features of diatopic varieties of German. Based on a variety-linguistic analysis and categorization conclusions are drawn about the German urban city dialect spoken in Pilsen until 1945 on which there have been no data available so far. At the same time, Hajšman's lexicographical documentation will be classified not only among other contemporary attempts to popularize the Pilsen colloquial language but also among similar tendencies of medial revival of (historical) city languages with German proportions that can be observed in Czech cities at former language borders (Brno, Ostrava) forming a linguistic memorial landscape.